Microtubule-targeting drugs rescue axonal swellings in cortical neurons from spastin knockout mice - Coralie Fassier; Anne Tarrade; Leticia Peris; Sabrina Courageot; Philippe Mailly; Cécile Dalard; Stéphanie Delga; Natacha Roblot; Julien Lefèvre; Didier Job; Jamilé Hazan; Patrick A. Curmi; et al. (The Company of Biologists, 2013)
SUMMARY Mutations in SPG4, encoding the microtubule-severing protein spastin, are responsible for the most frequent form of hereditary spastic paraplegia (HSP), a heterogeneous group of genetic diseases characterized by degeneration of the corticospinal tracts. We previously reported that mice harboring a deletion in Spg4, generating a premature stop codon, develop progressive axonal degeneration characterized by focal axonal swellings associated with impaired axonal transport. To further characterize the molecular and cellular mechanisms underlying this mutant phenotype, we have assessed microtubule dynamics and axonal transport in primary cultures of cortical neurons from spastin-mutant mice. We show an early and marked impairment of microtubule dynamics all along the axons of spastin-deficient cortical neurons, which is likely to be responsible for the occurrence of axonal swellings and cargo stalling. Our analysis also reveals that a modulation of microtubule dynamics by microtubule-targeting drugs rescues the mutant phenotype of cortical neurons. Together, these results contribute to a better understanding of the pathogenesis of SPG4-linked HSP and ascertain the influence of microtubule-targeted drugs on the early axonal phenotype in a mouse model of the disease.